Production of biocomposites file for packaging application - Mat Zain, Norashikin; Mohd Marzuki, Mohamed; Ibrahim, Mohd Zamri; Sueb, Mohd Shafiq; Mohd Arshad, Z. I. (2011)
This study will be focusing on fabrication of composite biodegradable film from chitosan blends with addition of antimicrobial agent. The film was characterized in term of morphology, physical, chemical and also the antimicrobial analysis. The chitosan solution was prepared by preparing chitosan solution and antimicrobial agent was added to the mixture. The solution was cast onto flat glass plate. The thickness of the film was adjusted using a casting knife. The film was left to dry at room temperature before peeled off. The fabricated film was analyzed and characterized using Scanning electron microscopes (SEM), Fourier transform infrared Spectroscopy (FTIR), Thermogravimetric analyzer (TGA) and Differential scanning calorimeter (DSC). The antimicrobial analyses were performed using Zone inhibition a_ssay and Liquid culture test. As a conclusion, chitosan blend biodegradable films shows the highest thermal resistant compared to control film. Other than that, the film also shows the greatest antimicrobial activity towards E. coli and B.subtilis.